Perbandingan Kinerja Lentur Balok Beton Bertulang Dengan Sambungan Lewatan Dan Sambungan Mekanis Tipe Cold Forged Sleeve With Parallel Threads - Jafar, Jafar; Rahmayuda, Bayu Setya (Universitas Semarang, 2025)
Steel rebar is generally 12 meters in length, so if more than that is required, it must be joined using methods such as lap splice, welded splice, or mechanical splice. This study compares the flexural strength of reinforced concrete beams without splice, with lap splice, and with Cold Forged sleeve with Parallel Threads (CFSPT) type mechanical splice, to assess the performance of each splice method. The study used beam specimens measuring 200 x 20 x 40 cm with a planned concrete quality f'c 25 MPa. Flexural strength testing resulted in a nominal moment value of 85.209 kNm for the normal beam, 92.952 kNm for the skip beam, and 82.305 kNm for the coupler beam. Based on the nominal moment value of the experiment, the lap splice beam has the highest value and the coupler connection beam has the lowest value. The resulting deflection of the normal beam tends to be higher than that of the lap splice beam and the coupler beam, which is 72.522 mm. While the maximum deflection produced by the lap splice beam and coupler beams is 44.876 mm and 40.191 mm, respectively. The ductility values of the normal beam, lapsplice beam, and coupler beam were 5.949; 3.257; 4.550, respectively.